THE IMPLEMENTATION OF “CATUR GURU” AS THE BASIS OF CHARACTER EDUCATION IN ELEMENTARY SCHOOL - I Nyoman Sueca; I Nyoman Temon Astawa; Ni Luh Sinar Ayu Ratna Dewi (International Journal of Instructions and Language Studies, 2023)
Purpose – This scientific paper aims to discuss a special approach of character education in elementary school, which covers both its urgency and implementation. Methodology – The data collection was carried out through document studies, observations, and in-depth interviews with teachers, parents, and socio-cultural experts. The data were analyzed qualitatively using pedagogical theories and Bourdeau’s theory of social action. Findings – The result showed that intensive character education is essential for elementary school students, since they are still at their golden age, which would promote the effectiveness of its implementation. Character education, for elementary school students, can be implemented based on the concept of Catur Guru, including developing the students’ character to respect; Guru Rupaka (parents), Guru Pengajian (school teacher), Guru Wisesa (government), and Guru Swadyaya (God Almighty). Significance – These four dimensions of Guru (the teachers of life) must be introduced synergistically in order to build the character of elementary school students in their house, school, society, and also their living environment. Character education was also expected to direct the students’ creativity, critical thinking, communication, and collaboration, toward kindness and peace. Other implications for educational purposes were also discussed.